GUIDANCE IN PROCESSING FISH FLOUR IN REALIZING THE WELFARE OF THE FEMALE FISHING COMMUNITY - Budiman, Ahmad; Bachtiar, Jusuf; Asiyah, Binti Nur; Khofifah, Laini; Isnawati, Adinda Putri Yesa (Yayasan Education and Social Center, 2024)
The utilization of fish catches in Besole Village has yet to be maximized. The catches are directly sold in the form of fresh fish to intermediaries and grilled fish that depend on tourists who come, so the catch depends on the price in the market. It is one of the reasons for conducting community service and assisting in utilizing assets owned by Besole Village. Processing catches is one of the efforts that is expected to improve the economy and realize prosperity because the processing results will have a higher selling value. This community service uses the Asset Based Community Development (ABCD) method. The female fisherman community is assisted in processing the catches. After assistance is provided, the community can process the catches into fish floss products that can be marketed for a long time and in a wide range. The practical implication of this activity is that the local government, village, and pokdarwis can monitor and ensure that the female fisherman community can maximize the sustainability of fish floss processing to support the welfare of families and communities